2006
DOI: 10.1108/17427370780000142
|View full text |Cite
|
Sign up to set email alerts
|

Energy‐efficient capacity‐constrained routing in wireless sensor networks

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…The routing of the data packets to the base station on these minimumcost paths is efficient, so long as the rate of information generation is low or the channel bandwidth is sufficiently high. Still, if the nodes generate data constantly and the bandwidth is constrained, then routing data on the minimum-cost paths can overload wireless links close to the base station [6]. Therefore, a routing protocol must take into consideration the wireless channel bandwidth limitations, otherwise, it might route the packets over highly-congested links and paths.…”
Section: Energy-efficient Route Selection Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The routing of the data packets to the base station on these minimumcost paths is efficient, so long as the rate of information generation is low or the channel bandwidth is sufficiently high. Still, if the nodes generate data constantly and the bandwidth is constrained, then routing data on the minimum-cost paths can overload wireless links close to the base station [6]. Therefore, a routing protocol must take into consideration the wireless channel bandwidth limitations, otherwise, it might route the packets over highly-congested links and paths.…”
Section: Energy-efficient Route Selection Policiesmentioning
confidence: 99%
“…Therefore, a routing protocol must take into consideration the wireless channel bandwidth limitations, otherwise, it might route the packets over highly-congested links and paths. This will lead to increase in congestion, increased delay and packet losses, which in turn will cause retransmission of packets, thereby, increasing energy consumption [6].…”
Section: Energy-efficient Route Selection Policiesmentioning
confidence: 99%
“…It is a kind of combination of maximum flow (getting as much flow as possible from the source to the sink) and shortest path (traveling from the source to the sink with minimum cost). The problem addressed in (Xu et al, 2008) has the same structure as that found in Patel et al (2006), but the objective is utility maximization, which is a nonlinear convex function of the transmission rate. The problem is solved using the Lagrangian method.…”
Section: Enhanced Flow Based Modelsmentioning
confidence: 99%
“…To ensure that the solution will not generate scenarios in which the traffic load is unfair for the nodes in the network, the flow transmitted by a node has to be less than a given fraction of the total flow generated by the network. Patel et al (2006) add the following two constraints to the basic version of the routing problem: (i) the link capacity constraint where the rate (the number of packets per unit time) at each link has to be smaller than its capacity, and (ii) the node capacity constraint where the number of packets that a node can process in a unit time has to be smaller than its given capacity. The proposed algorithm is centralized and aims to find a maximum flow with the smallest possible energy cost.…”
Section: Enhanced Flow Based Modelsmentioning
confidence: 99%
“…Ως εκ τούτου, όλα τα πρωτόκολλα δρομολόγησης θα πρέπει πάντοτε να λαμβάνουν υπόψη τους περιορισμούς που θέτει το εύρος του ασύρματου καναλιού, διότι, σε διαφορετική περίπτωση, τα πακέτα δεδομένων θα δρομολογούνται σε μονοπάτια και ζεύξεις όπου παρατηρείται πάρα πολύ μεγάλη συμφόρηση. Αυτό το γεγονός θα συμβάλει στην περαιτέρω αύξηση της συμφόρησης, στην αύξηση της χρονικής καθυστέρησης, αλλά και στην αύξηση απωλειών πακέτων, με άμεσο επακόλουθο την εκ νέου αποστολή πακέτων, και κατά συνέπεια στην αύξηση της κατανάλωσης ενέργειας[172].…”
unclassified